UNDERSTANDING LANGUAGE TOWARD A COMPREHENSIVE DEFINITION - Xaydarova Nigora,; Rakhmatillaeva Gulzirakhon, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: Language is more than a tool for communication; it shapes our thoughts,  beliefs,  and  relationships.  Through  language,  we  express  ideas,  share emotions, and form our understanding of the world. It influences how we see ourselves and how we interact with others in society. This article discusses why language matters and how it affects our perceptions, identities, and social connections. By examining examples  from  literature,  media,  and  everyday  life,  we  explore  the  powerful  role language plays in shaping both individual experiences and social dynamics.